The Effect of Using Talkpal AI on Improving the Arabic Vocabulary of Secondary School Students - Salwa Salsabila; Ihwan Rahman Bahtiar; Khotimmatun Nafi’ah (Program Studi Pendidikan Bahasa Inggris, Universitas Pendidikan Muhammadiyah Sorong, 2025)
This study aims to determine the effect of using Talkpal AI on improving Arabic vocabulary mastery among students at Al-Azhar Kelapa Gading Islamic High School. The background of this study is based on the low level of Arabic vocabulary mastery among students, which is caused by the use of learning media that is not interactive enough, thereby impacting students' low motivation to learn. In fact, the school has adequate supporting facilities, such as smart TVs in each classroom, which enable the application of technology-based learning media. This study uses a quantitative approach with a quasi-experimental method and a nonequivalent control group design. There were 44 students participating in the study, divided into an experimental class and a control class. Data collection techniques were carried out through observation and Arabic vocabulary tests. The results showed that the average posttest score of the experimental class (32.50) was higher than that of the control class (26.27). The Mann-Whitney test showed a significance value of 0.002 (< 0.05), which means that there is a significant effect of using Talkpal AI on improving students' Arabic vocabulary. Thus, Talkpal.ai is proven to be effective as an artificial intelligence-based learning medium in helping to improve students' mastery of Arabic vocabulary.